Battery charger with alphanumeric LCD module monitoring - Mohd Hapiz, Arbain (2008)
The objective of this project is to create a battery charger with alphanumerical LCD module monitoring, display the values of voltage during charging, and can charge most common rechargeable battery types. The design is separated into three basic parts, charging circuit, controller circuit and LCD monitoring screen. This charger is able to charge up to 8 batteries of AAA size at one time, able to protect the battery from overcharge and can present the voltage value. Using PIC16F876A as a brain of the system, all the processes are managed by the controller including the data that display on the LCD screen. User gives instruction to the controller by just pushing the push button near the controller, and view the LCD screen for menu option. Even with limited projected words that can be display on the LCD, this charger still has an interesting output that can be represented to user. Some of it are time counter and automatically stop the charging process before battery is overcharge.